Approximate solutions for nonlinear oscillation of a mass attached to a stretched elastic wire - Durmaz, Seher; Demirbag, Sezgin Altay; Kaya, Metin Orhan (Elsevier BV, 2011)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: nonlinear oscillator; He's frequency-amplitude method; parameter-expansion method; Nonlinear oscillations and coupled oscillators for ordinary differential equations; Nonlinear oscillator; Parameter-expansion method; He’s max–min approach; Computational Mathematics; Computational Theory and Mathematics; Modelling and Simulation; Motion of a rigid body with a fixed point; He’s frequency–amplitude method; Numerical methods for ordinary differential equations; He's Max-min approach